Penerapan Konseling Kelompok Teknik Assertive Untuk Meningkatkan Self-Esteem Siswa SMPN 1 Makassar - Artia Damaira; Rukiana Novianti Putri; Pertiwi Nurani (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to examine the effectiveness of group counseling using assertive techniques in improving students’ self-esteem at SMPN 1 Makassar. The research employed a quantitative experimental method with a one-group pretest–posttest design. The sample consisted of 12 students selected through purposive sampling based on low self-esteem criteria from a population of 1,437 students. Data were collected using a validated and reliable self-esteem questionnaire and analyzed through descriptive statistics, Kolmogorov-Smirnov normality test, and Wilcoxon signed-rank test using SPSS version 26. The results showed a significant improvement in students’ self-esteem after the intervention. Initially, 75% of students were categorized as having low self-esteem and 25% moderate, while after treatment, 100% of students reached a high self-esteem category. Statistical analysis revealed a significance value of 0.002 (<0.05), indicating that the null hypothesis was rejected and the alternative hypothesis accepted. The findings suggest that assertive group counseling effectively enhances students’ confidence, ability to express opinions, and self-worth. Therefore, this approach can be recommended as an effective intervention in school counseling services to foster positive self-esteem development among adolescents.